An Examination of the Developmental Impact of Continuing Destructive Parental Conflict on Young Adult Children. (April 2020) - Fozard, Emily; Gubi, Peter
This research investigates the impact of destructive parental conflict in continuously married parents, on young adult children. Four trainee or practicing counselors, who had personal experience of growing up in families in which there was continuing destructive parental conflict, were interviewed. The data were analyzed using interpretative phenomenological analysis. The findings resulted in four superordinate themes: feelings of loss, impact to family structure, trauma associated with the conflict, and impacts to personal and professional development, within which were 12 subordinate themes. Short-term impacts focused on mental health and self-esteem, and loss of security at home. Long-term impacts focused on future relationships, defensiveness, parent–child role-reversal, impacts to career, trauma, and parent–child relationships. The results demonstrate the necessity for support to be made available to children who are exposed to destructive parental conflict in parents who remain married, as well as to the adult children of continuing destructive parental conflict.